2014
DOI: 10.1111/ecog.00913
|View full text |Cite
|
Sign up to set email alerts
|

Species’ roles in food webs show fidelity across a highly variable oak forest

Abstract: Ecological communities are composed of many species and an intricate network of interactions between them. Because of their overall complexity, an intriguing approach to understanding network structure is by breaking it down into the structural roles of its constituent species. The structural role of a species can be directly measured based on how it appears in network motifs – the basic building blocks of complex networks. Here, we study the distribution of species’ roles at three distinct spatio‐temporal sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 51 publications
5
92
0
Order By: Relevance
“…Interestingly, Baker et al . () conclude that species generally have conserved motif roles (compared to random arrangements) which is somewhat similar to the high partner fidelity (compared to random partner utilization) found in pollination networks (Trøjelsgaard et al . ).…”
Section: Perspectivessupporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, Baker et al . () conclude that species generally have conserved motif roles (compared to random arrangements) which is somewhat similar to the high partner fidelity (compared to random partner utilization) found in pollination networks (Trøjelsgaard et al . ).…”
Section: Perspectivessupporting
confidence: 64%
“…; Baker et al . ). For host–parasitoid networks, it has been shown that species tend to have a particular motif role across space and time (more so than if interactions were arranged randomly), that networks, as a whole, contain non‐random subsets of all possible motif roles and that the collection of motif roles found in a particular network may change from year to year (Baker et al .…”
Section: Perspectivesmentioning
confidence: 97%
“…Based on this vector it is possible to identify species statistically that exhibit similar profiles. Motif positions tend to be well conserved both in time (Stouffer et al, ) and space (Baker et al, ), making them ideal candidates to be investigated alongside functional traits and phylogenetic history.…”
Section: What Can We Learn With Ecological Network?mentioning
confidence: 99%
“…We followed the methods outlined in Baker et al. () and determined species’ role conservation across lakes by performing a perMANOVA. Here, total dissimilarity D across all species and networks was calculated with D=1Ni=1N1j=i+1Neitalicij2 where N is the total number of species’ roles (across all species and lakes) and e ij is the distance between role i and role j .…”
Section: Methodsmentioning
confidence: 99%
“…) and how individual species roles are altered by interaction turnover Baker et al. (). Together, they have the potential to improve the predictive capacity of our network models.…”
Section: Introductionmentioning
confidence: 99%